Alternate Dispute Resolution Mechanisms in Healthcare in Mexico: Strengthening Alternative Pathways Against the Judicialization of Medicine - Genaro Vega Malagon; Fernando Jose Cruz Lopez; Lorena Yazmin Valeriano Hernandez; Jasein Haddad Cortes Ahumada; Gabriela Espinoza Cervantes (European Scientific Journal, ESJ, 2026)
Alternative dispute resolution mechanisms for medical disputes in Mexico are operated by the National Medical Arbitration Commission and the 29 autonomous state commissions through the Mexican Medical Arbitration Model. This specialized system is designed to resolve disputes between users and healthcare providers (public or private) free of charge, impartially, and confidentially, without resorting to the courts. The model is divided into progressive stages according to the complexity of the conflict:Orientation and Advice: Provides initial legal and medical information on the rights and obligations of both parties. Immediate Management: Seeks to resolve administrative or urgent care issues quickly through direct dialogue with the institution. Conciliation: Is a negotiation assisted by a neutral third party. If the parties reach an agreement, a settlement is signed that has the force of res judicata (equivalent to a court judgment). Arbitration: If no agreement is reached during conciliation, the parties may voluntarily submit to arbitration. The arbitrator reviews the medical record and issues a final decision called an award. Its main characteristics are: Voluntariness: Both parties must agree to participate in the process. Specialization: Cases are analyzed by multidisciplinary teams of medical and legal experts. Culture of Peace: It prioritizes communication and reparation of harm over punishment or legal confrontation. National Scope: In addition to the federal body, there are state commissions that apply this same model in the federal entities.